2019
DOI: 10.3389/fspor.2019.00013
|View full text |Cite
|
Sign up to set email alerts
|

A One-Season Prospective Study of Illnesses, Acute, and Overuse Injuries in Elite Youth and Junior Track and Field Athletes

Abstract: Conclusion: This study provides important information regarding the extent of health problem in Youth and Junior track and field athletes. This could help orient injury prevention measures. For injuries, it should be focused on muscle injuries, especially located on the hamstring, calf, and trunk. For illness, prevention measures could include: screening tests for airway problems, but also general illness prevention measures (e.g., drinking regularly, eating "safe" food, regular hand washing, decreasing contac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 32 publications
3
24
0
Order By: Relevance
“…For illnesses, the mean weekly prevalence reported within this study (8%) is predominantly lower than that reported in the comparable studies (range: 14-23%), [8][9][10] with the exception being a cohort of elite Irish adolescent endurance athletes (6.9%). 11 Differences between these studies may be explained by the longer follow-up period (52-weeks) used in two of the studies, 8 10 thus being representative of a full calendar year, in addition to the possibility that the smaller sample sizes (range: 25 to 76) used in these studies overestimate the prevalence of these health problems. [8][9][10][11] The fundamental methodological differences between other studies make any further comparison difficult.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For illnesses, the mean weekly prevalence reported within this study (8%) is predominantly lower than that reported in the comparable studies (range: 14-23%), [8][9][10] with the exception being a cohort of elite Irish adolescent endurance athletes (6.9%). 11 Differences between these studies may be explained by the longer follow-up period (52-weeks) used in two of the studies, 8 10 thus being representative of a full calendar year, in addition to the possibility that the smaller sample sizes (range: 25 to 76) used in these studies overestimate the prevalence of these health problems. [8][9][10][11] The fundamental methodological differences between other studies make any further comparison difficult.…”
Section: Discussionmentioning
confidence: 99%
“…11 Differences between these studies may be explained by the longer follow-up period (52-weeks) used in two of the studies, 8 10 thus being representative of a full calendar year, in addition to the possibility that the smaller sample sizes (range: 25 to 76) used in these studies overestimate the prevalence of these health problems. [8][9][10][11] The fundamental methodological differences between other studies make any further comparison difficult.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these six training groups, athletes were then selected according to the following inclusion criteria: (1) training at least 3 times a week and engaged in competitive athletics, (2) without any contraindications for competitive athletics activity, and (3) aged from 15 to 40 years. Athletes were included irrespective of their baseline injury status or history [16], because excluding athletes with injury would have resulted in a biased study population not representative of athletes, where injuries are frequent [2][3][4]17]. Informed written consent was obtained from all participants in the study, and in addition from their parents for those under the age of 18 years.…”
Section: Participantsmentioning
confidence: 99%
“…development should be evidence-informed [16]. Also, the few available studies usually focus on adolescent track and eld (athletics), only including distance running as a sub-sample [13,14,17,18].…”
mentioning
confidence: 99%